Analysis of alternative project financing and optimum financing mix for a mall project in kalimantan - Pratama TEdja, Aditya; A. A. Marimba, Percy (The Indonesian Journal of Business Administration, 2016)
Abstract - The main challenge of commercial development is to arrange the capital. Commercial real estate developments require a large amount of capital upfront, as a one-time investment, and the return on investment occurs over a long period of time. In this case, PT. Dharma Development, Tbk. has been facing a capital problem for this project. The purpose of this research is to explore some alternative financing options for the small and medium commercial real estate developers, and suggest the most suitable financing options for the case of this research. Other than that, the primary objective is to answer the research question â€œwhat is the alternative project financing model that feasible for the company and also aligns with the corporateâ€™s fundamental strategyâ€. With the characteristics of large-scale investment (long pay-back period and capital intensive), the financing of commercial real estate is even more difficult than residential real estate and also become crucial problem for the development of commercial real estate. To get better understanding the research will use several analysis techniques. First is to understand what are the available and financing practice in other countries and to review what is available in Indonesia. Exploration of financing practice in Indonesia relating to the regulation, tax and system capability become the focus of this research. This research discusses industry specific matter using several financial tools to support the decision making. Discounted rate will be used to do a valuation for every stakeholders in the project. It will determine how the capital structure would arrange. The technique use is capital budgeting. Capital budgeting is a process to analyze, evaluate and make decision. At the end of this final project writing, the author will provide a recommendation to find the best option to arrange this project in order to get highest profitability of this project.Â Keywords: Project Financing, Crowdfunding, Indonesia Real Estate, Partnership